2013
DOI: 10.3233/jae-2012-1600
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study on effect of process parameters on preparation of A356 aluminum alloy semi-solid slurry by electromagnetic stirring

Abstract: A two-dimensional model coupling of the electromagnetic field, the temperature field and the flow field of preparation of A356 aluminum alloy semi-solid slurry by electromagnetic stirring (EMS) was established. The Power Law Cut-Off (PLCO) model was used to model the semi-solid slurry. The effect of process parameters such as stirring frequency, stirring current, pouring temperature and crucible preheated temperature on the electromagnetic field, temperature field and flow field were investigated by finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…( 4) and exported to FLUENT solver as a momentum source term by a user-defined function (UDF). In addition, the PLCO viscosity model [17][18][19] was programmed in UDF and loaded on the model. The volume of the fluid model was used and the wall was viewed as a stationary wall under a no-slip shear condition in FLUENT.…”
Section: Materials and Ems Experimental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…( 4) and exported to FLUENT solver as a momentum source term by a user-defined function (UDF). In addition, the PLCO viscosity model [17][18][19] was programmed in UDF and loaded on the model. The volume of the fluid model was used and the wall was viewed as a stationary wall under a no-slip shear condition in FLUENT.…”
Section: Materials and Ems Experimental Proceduresmentioning
confidence: 99%
“…Hence, an appropriate viscosity model should be used to describe the variation in viscosity, which depends on slurry temperature and shear rate. The PLCO model is a modified one-phase power-law model with a shear cut-off, which can be used during EMS and the constitutive equations are shown as follows [17][18][19].…”
Section: Materials and Ems Experimental Proceduresmentioning
confidence: 99%
“…Therefore by eliminating the central part, the magnetic and temperature fields were more uniformly distributed in this narrow gap and thus a more uniform structure is obtained. A two-dimensional computational model of EMS has also been developed by Vanluu et al [9] to investigate the effects of process parameters on temperature and flow fields. They concluded that increasing stirring frequency and current will increase electromagnetic field and flow field density, but will not cause a uniform distribution of grains.…”
Section: Introductionmentioning
confidence: 99%
“…It includes preparation of semi-solid billet and forming steps [3]. Until now, in addition to magneto-hydrodynamic (MHD) stirring [4], cooling slope casting [5], liquidus/near liquidus casting [6], and strain-induced melt activation (SIMA) [7], recrystallization and partial melting (RAP) [8] is also a promising technology for preparing semi-solid billet.…”
Section: Introductionmentioning
confidence: 99%